The Effet of Using Quizizz for Vocabulary Mastery of SMKN 1 Pekanbaru Students - Cindy, Cindy; Prawati, Atni; Masyhur, Masyhur (CV. Rayyan Dwi Bharata, 2025)
This study explores the effect of using Quizizz on students’ vocabulary mastery at SMKN 1 Pekanbaru. A pre-experimental one-group pre-test and post-test design was applied to 37 students of class XI MPLB 3. Students were treated over four sessions using a scientific approach in Merdeka Curriculum, with Quizizz applied as an interactive learning and assessment tool. The vocabulary test focused on five elements from narrative texts: nouns, adjectives, mental verbs, action verbs, and conjunctions. The pre-test mean score was 65.56 (SD = 12.24), which increased to 87.41 (SD = 6.36) in the post-test. A paired sample t-test showed a statistically significant difference (t = -14.317, p .001), with a mean gain of 21.84 points. Quizizz’s game-based features appeared to boost students’ engagement and performance. The instrument’s reliability was confirmed by a KR-20 value of 0.91, indicating excellent internal consistency. These results demonstrate that Quizizz significantly improves vocabulary mastery in the context of narrative texts.